Ho Chi Minh’s thought about cultural diplomacy - Do Thi Ngoc Quy, Vu Kim Diem, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ho Chi Minh’s thought is a comprehensive and profound system of views on the fundamental issues of the Vietnamese Revolution, the result of the creative application and development of Marxism-Leninism in specific conditions of Vietnam in each stage of the revolution to ensure the victory of the resistance war and successful national construction. Today, domestic and world conditions have changed deeply, but Ho Chi Minh’s ideology in general and Ho Chi Minh’s ideology in particular still have great significance. The diplomatic culture was formed and developed with the process of forming his thoughts on the path of national liberation and socialist nation-building in Vietnam. This study provides a general overview of Ho Chi Minh’s thoughts on diplomatic culture and assesses the current status of the process of applying those perspectives to Vietnam's current diplomatic culture.